Família e política no RN: Alves, Maia e o suporte do Senado - Carvalho, Robson Vasconcelos (2018)
For more than seven decades, two family groups, Alves and Maia, have occupied, through /their representatives, important power spaces in Rio Grande do Norte, with special emphasis on the majority plan in the last four decades. In Colony, Empire, or even in phases before the Republic’s, no other family-political group has been so long-lived in the continuous occupation of power spaces in the potiguar’s soil. In the light of Machiavelli's realism, this dissertation analyzes the main means used by these families to remain in power over time, as well as their modus operandi, historical origins and bases of formation. In addition, we seek to identify the instruments of power they use and which strategies are chosen, with emphasis on the bipolarity’s logic. Among many instruments, two of them are highlighted: Parliamentary’s amendments and financing of electoral campaigns. Senators José Agripino Maia and Garibaldi Alves Filho were chosen as specific objects of analysis because they were, respectively, the representatives of the most expressive families in the analyzed period.